Pricing model of reactive power services of shared energy storage considering baseline power for renewable energy accommodation - Weiqiang Qiu; Changming Chen; Zhi Zhang; Yiting Wang; Lianfang Wang; Zhenzhi Lin; Li Yang (Energy Reports, 2022)
Driven by the gradual increase of the renewable energy installed capacity, shared energy storage (SES) has the potential to play an important role in the renewable energy accommodation scenario. In the process of accommodating renewable energy, SES users can also provide reactive power services to earn revenue and further improve the utilization rate of energy storage resources. In this context, a pricing model of reactive power services of SES is proposed in this paper to make SES users obtain reasonable revenue from the provided reactive power response capability. Firstly, based on the analysis of the cost composition, capacity constraint and application value of reactive power services, a cost-based time-variant capacity price is designed considering the investment cost and the opportunity cost of SES users. Moreover, the baseline power for renewable energy accommodation is proposed to quantify the opportunity cost caused by reactive power services in the renewable energy accommodation scenario. Finally, a case study based on the actual data of an SES trading pilot project in Qinghai, China, shows that the proposed pricing model can effectively reflect the costs of reactive power services which are highly coupled to the active power for renewable energy accommodation, and make SES users obtain the reasonable revenue covering the costs.